2007
DOI: 10.1111/j.1365-294x.2007.03363.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological patterns of introgression between two large white‐headed gull species in a zone of recent secondary contact

Abstract: Incomplete reproductive isolation promotes gene flow between diverging taxa. However, any gene encoding for traits involved in the reproductive barriers will be less prone to introgression than neutral markers. Comparing introgression rates among loci is thus informative of the number and functions of loci involved in the reproductive barriers. This study aimed at identifying possible mechanisms of restriction to gene flow across a zone of recent secondary contact between Larus argentatus and Larus cachinnans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 66 publications
(98 reference statements)
2
83
0
Order By: Relevance
“…The argument was that cluster II harboured more variation in L. argentatus and that it had been supported by nuclear AFLP (de Knijff et al 2001). This is also supported by the recent study by Gay et al (2007) on introgression between L. cachinnans (a descendant from the AraloCaspian refugium) and L. argentatus.…”
Section: Discussion (A) Phylogeographysupporting
confidence: 71%
See 3 more Smart Citations
“…The argument was that cluster II harboured more variation in L. argentatus and that it had been supported by nuclear AFLP (de Knijff et al 2001). This is also supported by the recent study by Gay et al (2007) on introgression between L. cachinnans (a descendant from the AraloCaspian refugium) and L. argentatus.…”
Section: Discussion (A) Phylogeographysupporting
confidence: 71%
“…Snell suggested that the claimed hybrids in Iceland were light-winged argentatus originating from Scandinavia and that no hybridization between the two species in Iceland occurs. Along with all the previously mentioned cases of hybridization in gulls, genetic research strongly suggests that gene flow among large white-headed gulls is in fact extensive in many parts of the world (Crochet et al 2002(Crochet et al , 2003Liebers et al 2004;Gay et al 2007). Thus, the haplotype and allele sharing in Icelandic L. hyperboreus and L. argentatus observed in this study should not be surprising.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The utility of nuclear markers for identification of species and their hybrids has been shown for introns (e.g., Pacheco et al 2002;Nadachowska and Babik 2009), single nucleotide polymorphisms (SNP; e.g., Väli et al 2010;Hohenlohe et al 2011), and microsatellites (e.g., Gay et al 2007;Väli et al 2010). A combined set of nuclear and mitochondrial markers may be the best option for species and their hybrids identification, especially in birds, when hybridizing species diverged recently and share a high proportion of alleles (e.g., Gay et al 2007;Väli et al 2010).…”
Section: Introductionmentioning
confidence: 99%